Helmintofauna de gatos (Felis silvestres catus, LINNAEUS, 1758) da região metropolitana de Cuiabá - Ramos, Dirceu Guilherme de Souza (2012)
Cats’ helminths are causing gastrointestinal, liver and lung diseases, and some of them have zoonotic potential, such as Ancylostoma spp. (cutaneous larva migrans) and Toxocara spp. (visceral and ocular larva migrans). In order to identify the helminth fauna, prevalence, the mean intensity of parasitism (MIP) and mean abundance population (MAP), 146 cats were necropsied from the metropolitan area of Cuiabá. Eleven species were identified in 98 animals comprising nematodes (Ancylostoma braziliense [50,68% - 53,64 – 27,18], A. tubaeforme [10,27% - 3,6 – 0,37], Toxocara cati [4,11% - 28,33 – 1,16], Physaloptera praeputialis [2,05% - 6,67 – 0,14], Capillaria feliscati [3,42% - 7,4 – 0,25] and Aelurostrongylus abstrusus [1,37%]), cestodes (Spirometra mansonoides [4,11% - 2,0 – 0,08], Dipylidium caninum [3,42% - 5,2 – 0,18] and Taenia taeniformis [0,68% - 1,0 – 0,01]), trematodes (Platynosomum fastosum [26,03% - 179,53 – 46,73]), and acanthocephalans (Centrorhynchus erraticus [3,42% - 3,2 – 0,11]), of which Ancylostoma spp. and P. fastosum were the most prevalent and higher MIP and MAP. This study shows occurrence of zoonotic species. The ocurrence of Centrorhynchus erraticus is the first time recorded in cats in Americas, and retracts an important finding to the understanding of the distribution of the genus Centrorhynchus which is common in species of wild animals.